Jonas Ethics of Responsibility A Necessary Reflection in Time of Pandemic (Global Journal of Human-Social Science, 2023)
This work aims to reflect about some aspects of the main work of the German philosopher Hans Jonas The Imperative of Responsibility In Search of Ethics for the Technological Age published in 1979 The Jonas Principle of Responsibility makes a critical assessment of modern technoscience considers that man started to maintain a relationship of responsibility with nature since it is under his power A new ethical proposition is needed that contemplates nature and not only the human person who also has a look not only at the present but at the future that is for future generations Thus Jonas ideas in addition to his contribution in the field of bioethics has an important contribution in environmental issues The possible impacts and imbalances that occur as a result of climate change or even the uncontrollable deforestation of the planet s already scarce forest reserves are known in addition to the repercussions on human health caused by the deterioration of the environment the Covid-19 pandemic could be a of its repercussions increasing human vulnerability and producing inequities as its effects are disproportionate among peoples around the world
Keywords: ethics of responsibility; hans jonas; environmental education; vulnerability; pandemiceno age